Analisis Pengaruh Video Animasi Lagu Anak Indonesia Terhadap Perkembangan Kosakata Pada Balita Berdasarkan Komponen Linguistik (International Forum of Researchers and Lecturers, 2024)
This research explores the potential of Indonesian animated children's songs videos in supporting vocabulary development in toddlers. Sampling from the